Research on Heilongjiang Supply Chain Finance Development Model Based on Fast k-Nearest Neighbor Algorithm - Zhang, Shuli (2019 International Conference on Virtual Reality and Intelligent Systems (ICVRIS), 2019)
In order to further tap Heilongjiang's financial market and stabilize the economic environment. A supply chain finance development model of Heilongjiang Province based on fast k-nearest neighbor algorithm is proposed. By calculating the current financial circulation coefficient of Heilongjiang supply chain, investigating the market share and potential mining ability of local supply chain, and combining the fast k-nearest neighbor algorithm to calculate the development potential of supply chain finance, the research on the development mode of Heilongjiang supply chain finance is realized. Finally, the experiment proves that the research method of Heilongjiang supply chain finance development model based on fast k-nearest neighbor algorithm has higher practicability and accuracy than the traditional method.